Opposite phenotypes of hypomorphic and Y766 phosphorylation site mutations reveal a function for Fgfr1 in anteroposterior patterning of mouse embryos - Partanen, Juha (Cold Spring Harbor Laboratory Press, 1998)
Intercellular communication is needed for both the generation of the mesodermal germ layer and its division into distinct subpopulations. To dissect the functions of fibroblast growth factor receptor-1 (FGFR1) during mouse gastrulation as well as to gain insights into its possible roles during later embryonic development, we have introduced specific mutations into the Fgfr1 locus by gene targeting. Our results show functional dominance of one of the receptor isoforms and suggest a function for the autophosphorylation of site Y766 in the negative regulation of FGFR1 activity. Y766F and hypomorphic mutations in Fgfr1 generate opposite phenotypes in terms of homeotic vertebral transformations, suggesting a role for FGFR1 in patterning the embryonic anteriorposterior axis by way of regulation of Hox gene activity.